2004
DOI: 10.1158/1078-0432.ccr-03-0127
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bladder Cancer in Urine by a Tumor Suppressor Gene Hypermethylation Panel

Abstract: Purpose: Bladder cancer is potentially curable in the majority of cases; however, the prognosis for patients with advanced disease at presentation remains poor. Current noninvasive tests such as cytology lack sufficient sensitivity to detect low-grade, low-stage tumors. Silencing of tumor suppressor genes, such as p16 INK4a , VHL, and the mismatch repair gene hMLH1, has established promoter hypermethylation as a common mechanism for tumor suppressor inactivation in human cancers. It is also a promising new ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
136
2
5

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 23 publications
5
136
2
5
Order By: Relevance
“…Most molecular biomarkers analysed to date, lack sufficient specificity or sensitivity for their widespread use, and require extensive genetic analysis preventing their routine clinical use (Molinie et al, 2001). A promising biomarker recently investigated is aberrant DNA promoter hypermethylation (Dulaimi et al, 2004). This epigenetic marker has potential benefits over previously analysed genetic investigations, as it occurs widely throughout cancerous cells (thus only several loci need analysis) and always affects the same genomic loci (promoter regions) allowing minimal analysis.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Most molecular biomarkers analysed to date, lack sufficient specificity or sensitivity for their widespread use, and require extensive genetic analysis preventing their routine clinical use (Molinie et al, 2001). A promising biomarker recently investigated is aberrant DNA promoter hypermethylation (Dulaimi et al, 2004). This epigenetic marker has potential benefits over previously analysed genetic investigations, as it occurs widely throughout cancerous cells (thus only several loci need analysis) and always affects the same genomic loci (promoter regions) allowing minimal analysis.…”
mentioning
confidence: 99%
“…Silencing of tumour suppressor genes (TSG) associated with aberrant hypermethylation has been shown to be a molecular pathway for human cancer development (Herman and Baylin, 2003). As promoter hypermethylation occurs frequently in UC (Catto et al, 2005), several authors have investigated its detection in exfoliated urinary cells as a novel diagnostic test (Maruyama et al, 2001;Chan et al, 2002;Dulaimi et al, 2004;Friedrich et al, 2004). Recently, Dulaimi et al (2004) found that analysis of hypermethylation using a panel of TSG's yielded superior results to cytology in the detection of bladder cancer.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Klinisch bedeutsam ist trotz des überwiegend gu ten Verlaufs der papillären Tumoren eine hohe Rezidivrate (50-70%), was vor allem auf multifokale Tumorherde zurückzu führen ist. Problematisch ist hierbei ins besondere, dass 10-20% dieser Tumoren zu (Muskel ) invasiven Stadien rekurrie ren können [3].…”
Section: Hintergrund Und Fragestellungunclassified